Optimized serum ferritin prediction of iron overload in transfusion-dependent thalassemia: likelihood ratio and age-adjustment approach - Lutfi Ali Kurban; Bashayer Khamis Almarri; Maitha Helal Alshamsi; Shahd Shehadeh Abdelrahman; Sara Ghumail Alwahshi; Qays Alhorani; Rizwan Syed; Omran Bakoush (Annals of Saudi Medicine, 2023)
BACKGROUND: Early detection of iron overload in transfusion-dependent thalassemia (TDT) patients is critical to prevent complications and improve survival. OBJECTIVES: Evaluate the utility of serum ferritin (SF) in the prediction of hepatic and myocardial iron overload (HIO and MIO) compared to T2*-MRI. DESIGN: Retrospective SETTINGS: Governmental hospitals. PATIENTS AND METHODS: Patients with TDT who had T2*-MRI examinations between January 2016 to October 2019 were included. The predictive value of SF for detection of HIO and MIO was assessed by measuring area under the curve (AUC). A sample size of 123 cases was calculated to detect a correlation of 0.25 with 90% power and a two-sided type I error of 0.05. MAIN OUTCOME MEASURES: The correlation between SF and estimated hepatic iron concentration. SAMPLE SIZE: 137 TDT patients who required regular blood transfusions. RESULTS: The predictive value of SF was excellent for detection of HIO (AUC=0.83-0.87) but fair for detection of MIO (AUC=0.67). The two independent predictors of MIO were age and SF. The log of (age × SF) enhanced the SF predictive value for MIO (AUC=0.78). SF values of 700 and 1250 mg/L effectively excluded mild and moderate HIO with a sensitivity of 97.8% and 94.2%, respectively (LR−=0.1). While SF values of 1640 and 2150 mg/L accurately diagnosed mild and moderate HIO with a specificity of 95.55% and 96.4%, respectively (LR+>10). A log of (age × SF) cut-off value of 4.15 effectively excluded MIO (LR−=0.1), while a value of 4.65 moderately confirmed MIO (LR+=3.2). CONCLUSIONS: SF is an excellent predictor of hepatic IO in TDT. Age adjustment enhanced its myocardial IO predictive accuracy. Likelihood ratio-based SF cut-off values may help clinicians in risk stratification and treatment decision-making. LIMITATIONS: The laboratory data were gathered retrospectively and although the risk of selection bias for T2*-MRI examination is thought to be low, it cannot be ignored. CONFLICT OF INTEREST: None.